The Use of Educational Apps as Didactic Tools in Teaching English as a Second Language - Mokhirakhon Djaxangirovna Tadjiyeva (Journal of Higher Education and Academic Advancement, 2024)
This research paper aims to investigate the effectiveness of educational apps as didactic tools in teaching English as a second language (ESL) and their impact on student learning outcomes. Educational apps are interactive and engaging tools that can be used to support language learning outside the classroom. This study will examine how educational apps can be used to enhance student engagement and promote language learning. The research will be conducted through a mixed-methods approach, including a literature review and a quasi-experimental study. The literature review will synthesize previous studies on the use of educational apps in ESL instruction and their impact on student learning outcomes. The quasi-experimental study will involve comparing the learning outcomes of students who use educational apps with those who receive traditional classroom instruction. The study aims to provide insights into how educational apps can be effectively integrated into ESL instruction to enhance student learning outcomes. The research findings will contribute to the existing body of knowledge on educational apps and ESL instruction and provide recommendations for teachers to effectively use educational apps as a didactic tool to enhance student learning outcomes.